EAP Students’ Perceptions of Extensive Listening - Dwi Yulianto Nugroho (Metathesis: Journal of English Language, Literature, and Teaching, 2020)
Compared to other language skills, listening is a language skill that is often ignored and forgotten in English for Academic Purposes (EAP) classes. Thus, there should be more room for teaching listening in EAP classes. Extensive listening (EL) could be one alternative that English teachers can do to give more room for teaching listening. This descriptive study investigated 19 EAP students' perceptions of an EL program. Research data showed that most students have positive perceptions of EL. EL provides a fun but meaningful activity for students. Most of the students agree that EL can improve their listening fluency and vocabulary and expose them to various English accents. In addition, they state that EL helps them become more confident to talk to other people in English and they want to do EL in the future although nobody asks them. Therefore, EL is a promising program to be implemented in EAP classes.